2021
DOI: 10.12659/msmbr.927834
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Lactate, Troponin, and N-Terminal Pro-B-Type Natriuretic Peptide Are Predictors of Mortality in Patients with Sepsis and Septic Shock: A Retrospective Cohort Study

Abstract: Background Serum lactate, troponin, and N-terminal pro-B-type natriuretic peptide (NT-proBNP) have been proposed to be useful prognostic indicators in patients with sepsis and septic shock. This study aimed to evaluate the predictive ability of these biomarkers and assess how their prognostic utility may be improved by using them in combination. Material/Methods A retrospective review of the medical records of 1242 patients with sepsis and septic shock who were admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Detailed characteristics of the included studies can be found in Table 1. Among the included studies, before-treatment blood lactate measured values had been documented in 78 studies [6,[9][10][11][12][13][15][16][17][18][19]. Also, most of them provided data on the association between nonsepsis, sepsis, severe sepsis and septic shock and different blood lactate values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed characteristics of the included studies can be found in Table 1. Among the included studies, before-treatment blood lactate measured values had been documented in 78 studies [6,[9][10][11][12][13][15][16][17][18][19]. Also, most of them provided data on the association between nonsepsis, sepsis, severe sepsis and septic shock and different blood lactate values.…”
Section: Resultsmentioning
confidence: 99%
“…However, there exists inconsistency in the reference criteria for predicting the prognosis of sepsis in cases of elevated lactate levels. While certain studies emphasized an initial lactate level greater than 2.0 mmol/L as indicative of elevated lactate levels [15,16], others suggested that elevated lactate levels are defined by an initial lactate level exceeding 4.0 mmol/L [17][18][19]. Furthermore, there is no relevant quantitative metaanalysis focusing on different blood lactate level to predict different outcomes in sepsis, such as severe sepsis and septic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms of myocardial ischemia resulting from coronary artery pathology include coronary artery spasm [ 57 ] or dissection [ 58 ], as well as coronary embolism [ 59 ]. Ischemic myocardial damage may also result from disproportions between oxygen supply and demand due to conditions such as bradyarrhythmia [ 60 ], tachyarrhythmia [ 61 ], poorly controlled hypertension resulting in left ventricular hypertrophy [ 62 ], respiratory failure [ 63 ], hypotension [ 64 ], shock (different types, both cardiogenic and non-cardiogenic) [ 65 , 66 , 67 ], or severe anemia [ 68 ]. Moreover, important diseases in which elevated cardiac troponin levels are observed include heart failure [ 69 , 70 , 71 ], myocarditis [ 72 , 73 ], and chronic renal failure [ 74 , 75 ].…”
Section: Cardiac Troponin Blood Level In Acute Cardiovascular Eventsmentioning
confidence: 99%
“…Notably, its secretion is also influenced by the inflammatory response[ 20 , 21 ]. NT-proBNP is increasingly used as a biomarker in pediatric conditions that combine myocardial stress and inflammatory diseases, such as sepsis or Kawasaki disease[ 22 - 24 ]. Therefore, it is not surprising that NT-proBNP levels are markedly raised in almost all patients with MIS-C, where the proposed mechanism for the cardiovascular dysfunction is myocardial inflammation related to systemic inflammation with a cytokine storm[ 4 , 8 , 11 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%